The Role Of Sangeh Customary Village Towards The Development Of Sangeh Tourism Attraction - Paristha, Ni Putu Tiya; Mirayani, Ni Kadek Sri; Wea, Ernesta; Selamet, I Wayan Agus; Satia Negara, I Made Weda (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2024)
In recent times, customary villages have undergone changes and now serve dynamic functions, not only centered around customs and religion, but also actively participating in the economic sector. One example is the Sangeh Tourist Attraction, managed by the customary village while still prioritizing the preservation of nature and community culture. This research was carried out with the aim of determining the role of customary villages in the development of Sangeh Tourism Attraction. The analysis used in this study was qualitative descriptive. Data were gathered using observation, interviews, and a review of the literature. The outcomes showed that Sangeh tourism attraction has natural, cultural, and spiritual tourism potential that can be developed as a tourist attraction, the role of customary village in the development of Sangeh tourist attraction is very large and becomes a key point. The role of customary villages in the development of Sangeh Tourism Attraction is to prepare tourist facilities, establish cooperation with the Badung Regency Tourism Office, submit income distribution rules for Sangeh Tourism Attraction, preserve Alas Pala, supervise tourism implementation, implement, and fund development and arrange Sangeh Tourism Attraction.